Promoter PPSP1–5-BnPSP-1 From Ramie (Boehmeria nivea L. Gaud.) Can Drive Phloem-Specific GUS Expression in Arabidopsis thaliana - Wang, Yunhe; Bao, Yaning; Zheng, Yancheng; Guo, Ping’an; Peng, Dingxiang; Wang, Bo (Frontiers in Genetics, 2020)
Isolation of phloem-specific promoters is one of the basic conditions for improving the fiber development and resistance of ramie phloem using genetic engineering. In this study, we isolated a ramie endogenous promoter (named PPSP1-BnPSP-1) and analyzed the function of its truncated fragments in Arabidopsis. The results show that PPSP1-BnPSP-1 can drive the GUS reporter gene to be specifically expressed in the veins of Arabidopsis. After abiotic stress treatment of the independent Arabidopsis lines carrying PPSP1-BnPSP-1 and its truncated fragments, only PPSP1-5-BnPSP-1 (-600 bp to -1 bp region of PPSP1-BnPSP-1) is stably expressed and exhibits phloem specificity. Our findings suggest that PPSP1-5-BnPSP-1 can be used as a phloem specific promoter for further research.